PANI nanofibers-supported Nb2CTx nanosheets-enabled selective NH3 detection driven by TENG at room temperature - Wang, Si; Liu, Bohao; Duan, Zaihua; Zhao, Qiuni; Zhang, Yajie; Xie, Guangzhong; Jiang, Yadong; Li, Shaorong; Tai, Huiling (Sensors and actuators. B, Chemical, 2021)
•A novel Nb2CTx/PANI-based NH3 sensor directly driven by a facile TENG is proposed.•The Nb2CTx/PANI-2 sensor exhibits a superior sensitivity (2.87 % ppm−1) toward a wide sensing range of 1–100 ppm NH3.•High RH influence on sensing response of the Nb2CTx/PANI-2 sensor is 8.94 times lower than that of PANI one. As a new member of the MXene family, two dimensional (2D) niobium carbide MXene (Nb2CTx) holds a promising potential in gas detection due to the abundant surface terminated groups and large specific surface area. In this work, a selective NH3 sensor based on polyaniline (PANI) nanofibers-supported Nb2CTx nanosheets (Nb2CTx/PANI) directly driven by a facile triboelectric nanogenerator (TENG) is proposed to provide a possible method for enhancing the NH3-sensing response. In addition, the gas sensing properties have been optimized by regulating different spray volumes of Nb2CTx nanosheets. Test results demonstrate that the NH3-sensing response and the response speed of the Nb2CTx/PANI-2 sensor have been evidently improved, indicating a good linear response toward a wide sensing range of 1–100 ppm NH3 at room temperature (∼25℃) under 87.1 % relative humidity (RH). Moreover, the influence of high humidity on gas sensing response of the Nb2CTx/PANI-2 sensor has been efficiently reduced due to the occupied active sites for water adsorption caused by intermolecular hydrogen bonds between PANI and Nb2CTx. Finally, mechanism of the enhanced gas sensing properties has been further investigated, which should be mainly attributed to the gas sensing improvement effect of p-n junction. This work is expected to offer a useful reference for the development of high-performance Nb2CTx/polymer-based gas sensors.